Niacin exacerbates β cell lipotoxicity in diet-induced obesity mice through upregulation of GPR109A and PPARγ2: Inhibition by incretin drugs - Zhang, Xiaojing; Zhu, Baoyi; Lin, Peibin; Liu, Xiaoping; Gao, Jun; Yin, Dazhong; Zeng, Jianwen; Liao, Baojian; Kang, Zhanfang (Frontiers in Endocrinology, 2022)
The widely used lipid-lowering drug niacin was reported to increase blood glucose in diabetes. Niacin receptor GPR109A is expressed in  cells, but how does niacin regulate β Cell function is not completely clear, especially in diabetic patients. lipotoxicity is an important characteristic of diabetes. This study armed to investigate the effect of niacin on β cell lipotoxicity in vitro and in vivo. In INS-1 β cells, palmitate significantly increased GPR109A mRNA expression and protein level. MTT and apoptosis analysis showed that niacin further increased the cytotoxicity and apoptosis induced by palmitate. Quantitative PCR results showed that niacin further increased the expression of GPR109A and PPARγ2 in the presence of palmitate. Silencing GPR109A by siRNA in INS-1 cells can decrease the expression of PPARγ and PPARγ2 induced by palmitate alone or in combination with niacin, and correspondingly reduce the apoptosis exacerbated by niacin in the presence of palmitate. Interestingly, GLP-1 receptor agonist exendin-4 can reduce the expression of GPR109A and PPARγ2 and alleviate niacin induced lipotoxicity and apoptosis in INS-1 cells. In diet-induced obesity (DIO) mouse model, niacin treatment resulted in elevated blood glucose, impaired glucose tolerance and insulin secretion, accompanied by the change of islets morphology and the decrease of β cell mass. The combination of niacin and DPP-4 inhibitor sitagliptin can improve glucose tolerance, insulin secretion and islet morphology and β cell mass, even better than sitagliptin alone. Our results show that niacin increased β cell lipotoxicity partially through upregulation of GPR109A and PPARγ2, which can be alleviated by incretin drugs. We provide a new mechanism for niacin to induce hyperglycemia, and suggest that the combination of niacin and incretin may have better blood glucose and lipid control effect in clinical practice.